Two-stage treatment with sliding fibular flap technique for chronic infected nonunion of the tibia - Kapukaya, Rana (Chin J Traumatol, 2020)
PURPOSE: To assess the effectiveness of two-stage treatment with the fibular sliding technique in chronic infected nonunion of the tibia. METHODS: The study included patients who were diagnosed with long-term chronic infected tibial nonunion following trauma and treated with the two-stage technique between January 2010 and November 2017. Patients with (1) intra-articular fractures of the distal third of the tibia and fibula, (2) pathological fracture resulting in bone loss or (3) neurological and vascular pathologies of the limbs were excluded. The operation consisted of two stages and the main goal in the first stage was to control the infection and in the second stage to control the healing of the bone. Functional & radiographic results and complications were evaluated according to Paley's criteria. RESULTS: The patients comprised 14 males and 5 females with a mean age of 37.4 years (range, 21–52 years). Patients were followed up for an average of 27 months (range, 15–38 months). The microorganisms produced from these patients were Staphylococcus aureus in 13 patients, Pseudomonas aeruginosa in 4 patients and no bacteria in 2 patients. After the first stage operation, superficial skin necrosis developed in 1 patient. In another patient, there was a persistent infection, although union was achieved. For the entire patient group, union was observed at the end of 7.44 months (range, 7–11 months). Based on Paley's criteria, there were 16 (84.2%) patients with excellent scores, 2 (10.5%) good scores and 1 (5.3%) fair scores radiologically; while regarding the tibial function, 15 (78.9%) patients had excellent scores, 3 (15.8%) good scores, and 1 (5.3%) fair scores. No patients had poor radiological or functional score. CONCLUSION: Two-stage treatment can be considered as an alternative for fractures in regions that are susceptible to many and persistent complications, such as the tibia. This technique has the advantages of short operation time, minimal blood loss, no excessive tissue damage and not very technique-demanding (a short learning curve with no requirement for an experienced team).